TECHNOLOGY INTERVENTION TO STUDY THE MOBILITY ISSUES OF THE ELDERLY - Sayantani Kayal (Ageing and society: The Indian journal of gerontology, 2014)
This initiative is intended for designing a healthcare model for the elderly living alone with the help of tri-axial accelerometer. With age motor functions of human body declines, causing mobility problems. This causes difficulties in the performance of the Activities of Daily Living (ADL) and Instrumental activities of Daily Living (IADL). The measure of wellness depends on how much independent the elderly are in the performance of ADL & IADL. In this project tri-axial accelerometer is used to measure the performance of ADL & IADL equated to certain scientific parameters in the bio-mechanics of the body. With the help of Bluetooth, accelerometer uploads the data in Personal computer. One program has been developed to capture the data and relay it to the care giver (May be a professional, Son, Daughter or any friend). With several trials, threshold value of bio-mechanical data is defined. If the relayed data exceeds the threshold value, care giver extends medical intervention to the elderly person under observation.